Numeration Literacy Capability Based on The Assimilation and Accommodation Framework Reviewed from Students' Cognitive Style - Inda Fitriana; Nizlel Huda; Rohati Rohati (MASI Mandiri Edukasi, 2025)
Numeracy literacy is one of the essential skills developed in mathematics learning, as it supports critical thinking and problem-solving abilities in daily contexts. However, many students still struggle to apply mathematical symbols and strategies effectively. This study aims to analyse students’ numeracy literacy skills in solving systems of linear equations in two variables (SPLDV) by considering reflective and impulsive cognitive styles through the assimilation and accommodation framework. This research employed a qualitative descriptive approach with eighth-grade students at MTs N 2 Batang Hari as participants. Subjects were selected using the Matching Familiar Figures Test (MFFT) to identify reflective and impulsive cognitive styles. Data were collected through numeracy literacy test questions, think-aloud protocols, and semi-structured interviews. Students’ responses were analysed based on indicators of numeracy literacy and their cognitive processes of assimilation and accommodation. The findings indicate that reflective students (R1 and R2) could analyse information accurately, employ mathematical symbols appropriately, construct SPLDV models, and conclude solutions logically. They predominantly demonstrated assimilation processes, showing careful and systematic reasoning. In contrast, impulsive students (I1 and I2) could identify information but struggled to use symbols and formal methods, often relying on guessing strategies. Their responses reflected accommodation processes, with lower accuracy and incomplete reasoning. In conclusion, reflective students achieved proficient numeracy and literacy skills, while impulsive students remained at a basic level. These results highlight the importance of tailoring instructional strategies to students’ cognitive styles to strengthen numeracy literacy competencies.